Evaluasi Keadaan Lingkungan di Destinasi Pulau Tidung Jakarta - Ghani, Yosef Abdul; Hamzah, Faizal; Pemala, Ricky; Fitriani, Arin Melina (JURNAL MEDIA WISATA: Wahana Informasi Pariwisata, 2019)
Environmental evaluation is not an official examination required by a statutory regulation, but rather a proactive effort carried out consciously to identify environmental problems that will arise so prevention efforts can be carried out. The scope of this environmental evaluation activity comes from the 1994 Minister of Environment Decree of the Republic of Indonesia concerning General Guidelines for the Implementation of Environmental audits as the basis of the variables to be evaluated. Data collection is done by interviewing 10 local people, Library Study, and Direct Observation to identify or look for historical information, a series of businesses and activities of local communities, environmental damage and Destination Management of Tidung Island. The results of this study found that Tidung Island began to develop as a tourist destination starting in 2009, with tourism activities mostly centered on the large Tidung Island, while the small Tidung Island became a conservation area managed by the government. Most of the local people of Tidung Island live depend on tourism activities, they facilitate tourists by building several tourism facilities and infrastructure. At present the environmental conditions in Pulau Tidung are undergoing a slight change, for example the marine ecosystem which can usually be overgrown with seaweed, currently cannot and is being tested for replanting, and the garbage at several coastal points on Tidung Island is large and small, slightly reducing the beauty of the island Tidung.